2016
DOI: 10.1037/emo0000119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compassion meditation on a psychological model of charitable donation.

Abstract: Compassion is critical for societal wellbeing. Yet, it remains unclear how specific thoughts and feelings motivate compassionate behavior, and we lack a scientific understanding of how to effectively cultivate compassion. Here, we conducted 2 studies designed to a) develop a psychological model predicting compassionate behavior, and b) test this model as a mediator of a Compassion Meditation (CM) intervention and identify the "active ingredients" of CM. In Study 1, we developed a model predicting compassionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 85 publications
4
81
0
Order By: Relevance
“…Separately, we found that self-reported care and distress both positively predicted increased donation, although care was a stronger predictor. This both confirms previous reports that increased distress predicts helping (i.e., Ashar, Andrews-Hanna, Yarkoni, et al, 2016) and lends credence to prior arguments that empathic care rather than distress is the primary motivator of altruism (Ashar, Andrews-Hanna, Dimidjian, et al, 2016; Batson, 2011; Singer & Klimecki, 2014). …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Separately, we found that self-reported care and distress both positively predicted increased donation, although care was a stronger predictor. This both confirms previous reports that increased distress predicts helping (i.e., Ashar, Andrews-Hanna, Yarkoni, et al, 2016) and lends credence to prior arguments that empathic care rather than distress is the primary motivator of altruism (Ashar, Andrews-Hanna, Dimidjian, et al, 2016; Batson, 2011; Singer & Klimecki, 2014). …”
Section: Discussionsupporting
confidence: 89%
“…It was also positively correlated with empathic care, though more weakly than in the original neuroimaging sample. These results suggest that the empathic distress marker is most closely related to a non-specific negative arousal in response to others’ suffering, in line with how we and others have conceptualized empathic distress (Ashar, Andrews-Hanna, Yarkoni, et al, 2016; Ashar, Andrews-Hanna, Dimidjian, et al, 2016; Batson, 2011; Singer & Klimecki, 2014). …”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This may partly explain why clinical outcomes are heterogenous, and effect sizes of mindfulness-based interventions are moderate 17 . The framework can thus be adapted to measure other meditative attentional qualities (e.g., meta-awareness 33 and nonjudgment 24,25 ), as well as different types of meditation practice (e.g., open monitoring 3,7 and compassion 4,6 ), and be used to track person-specific skills and clinical outcomes. By developing measures to precisely assess the attentional qualities cultivated by meditation, we will gain the measurement power needed to rigorously test the mechanisms through which meditation may improve health and well-being.…”
Section: Discussionmentioning
confidence: 99%